Determinants of Early Initiation Among Deviants - Lee, Ching Yin; Zakaria, Abd Razak; A. Malik, Maisarah (American Scientific Publishers, 2017)
This study was carried out to examine the determinants of early initiation in deviance. The interest of the study was to identify the extent to which stress and depression, religious factors, school factors and early victimization contribute to the early initiation among deviants. The samples consist of 240 male inmates from Serendah Cure and Care Rehabilitation Centre. A questionnaire was administered to the sample. It requires information of deviant’s background and the frequency of circumstances in terms of stress and depression, religious factor, school factor and early victimization affected them before the prohibited substance onset. The results have shown that the combination of changes in religious factors, early victimization, stress and depression and school factors contribute 43.3 percent changes in the age of prohibited substance initiation among deviants. Particularly, an increment in the combination of religious factors, early victimization, stress and depression and school factors contribute a 43.3 percent earlier in the initiation age among deviants.